2017
DOI: 10.18805/lr-3708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal processing on anti nutritional factors and in vitro bioavailability of minerals in desi and kabuli cultivars of chick pea grown in North India.

Abstract: Genetic variation has a profound effect on the nutritional and anti nutritional profile of pulses. Thus, investigating this fact, comparison of five desi and four kabuli varieties of chickpea were done to assess the effect of genetic variation on the anti nutritional factors, bioavailability of minerals and the influence of hydrothermal (autoclaving, microwave cooking, boiling) and dry roasting processing methods. Results showed that large variability exist in antinutritional and mineral content of selected ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 17 publications
(20 reference statements)
5
14
0
Order By: Relevance
“…Similarly, the highest Fe, Cu, and Mn content was also observed after extrusion treatment. Sharma et al (2018) also reported an increase in the iron content of desi and kabuli chickpea after thermal processing. Pronounced increase in the mineral content after extrusion processing can be ascribed to better extraction of bound mineral owing to the disruption of cellular structure.…”
Section: Impact Of Processing Treatments On Biofunctional Characterismentioning
confidence: 85%
“…Similarly, the highest Fe, Cu, and Mn content was also observed after extrusion treatment. Sharma et al (2018) also reported an increase in the iron content of desi and kabuli chickpea after thermal processing. Pronounced increase in the mineral content after extrusion processing can be ascribed to better extraction of bound mineral owing to the disruption of cellular structure.…”
Section: Impact Of Processing Treatments On Biofunctional Characterismentioning
confidence: 85%
“…Roasting of legumes also reduced the phytic acid. The inherent phytase activity on cereals is believed to be activated during treatment (Sharma et al, 2018).…”
Section: Anti-nutritional Factormentioning
confidence: 99%
“…The total polyphenolic contents of the adzuki beans were measured using the Folin-Ciocalteu method (Sharma et al, 2017). Briefly, standards or extracts (50 l) were mixed with 1,000 l of a sodium carbonate solution (2%, w/v, Sigma-Aldrich, St. Louis, MO, USA) and 50 l of Folin-Ciocalteu reagent (50%, v/v, Sigma-Aldrich).…”
Section: Determination Of Total Phenolics and Flvanoidsmentioning
confidence: 99%